Clinical and Functional Characteristics of Subjects with Asthma, COPD, and Asthma-COPD Overlap: A Multicentre Study in Vietnam - Sy Duong-Quy; Huong Tran Van; Anh Vo Thi Kim; Quyen Pham Huy; Timothy J. Craig (Canadian Respiratory Journal)
Introduction. Subjects with asthma-chronic obstructive pulmonary disease (COPD) overlap (ACO) share common features of patients with asthma and COPD. Our study was planned to describe the clinical and functional features of subjects with ACO compared to asthma and COPD patients. Subjects and Methods. Study subjects who met the inclusion criteria were classified into three different groups: asthma, COPD, and ACO groups. All study subjects underwent clinical examination and biological and functional testing. They were then followed for 6 months to evaluate the response to conventional treatment. Results. From March 2015 to March 2017, 76 asthmatic (mean age: 41 ± 22 years), 74 COPD (59 ± 13 years), and 59 ACO (52 ± 14 years) subjects were included. The percentage of subjects with dyspnea on excretion in the ACO group was higher than that in asthma and COPD groups (P<0.001 and P<0.05, resp.). Subjects with COPD and ACO had significant airflow limitation (FEV1) compared to asthma (64 ± 17% and 54 ± 14% versus 80 ± 22%; P<0.01 and P<0.01, resp.). The levels of FENO in subjects with asthma and ACO were significantly higher than those in subjects with COPD (46 ± 28 ppb and 34 ± 12 ppb versus 15 ± 8 ppb; P<0.001 and P<0.001, resp.). VO2 max and 6MWD were improved in study subjects after 6 months of treatment. Increased CANO and AHI > 15/hour had a significant probability of risk for ACO (OR = 33.2, P<0.001, and OR = 3.4, P<0.05, resp.). Conclusion. Subjects with ACO share the common clinical and functional characteristics of asthma and COPD but are more likely to have sleep apnea. The majority of patients with ACO have a favourable response to combined treatment.